2015
DOI: 10.9778/cmajo.20150056
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of clopidogrel, prasugrel and ticagrelor for dual antiplatelet therapy after acute coronary syndrome: a decision-analytic model

Abstract: Background: The use of prasugrel or ticagrelor as part of dual antiplatelet therapy with acetylsalicylic acid after acute coronary syndrome (ACS) improves clinical outcomes relative to clopidogrel. The relative cost-effectiveness of these agents are unknown. We conducted an economic analysis evaluating 12 months of treatment with clopidogrel, prasugrel or ticagrelor after ACS. Methods:We developed a fully probabilistic Markov cohort decision-analytic model using a lifetime horizon, from the perspective of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Both have demonstrated superior efficacy compared with clopidogrel, albeit without prospective genotype substratification and at increased bleeding risk and higher medication costs [2]. Clinical trial results have also informed cost-effectiveness analysis (CEA) of alternative antiplatelets versus clopidogrel [9][10][11][12] and of CYP2C19 genotype-guided DAPT [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Both have demonstrated superior efficacy compared with clopidogrel, albeit without prospective genotype substratification and at increased bleeding risk and higher medication costs [2]. Clinical trial results have also informed cost-effectiveness analysis (CEA) of alternative antiplatelets versus clopidogrel [9][10][11][12] and of CYP2C19 genotype-guided DAPT [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, traditional cost-effectiveness modelling was not appropriate for the design of this study. However, we used cost estimations using methods similar to those utilized in prior similar studies [ 19 , 26 ]. Nonetheless, it is important to state that the cost savings reported in our study are estimates and not based on exact data (for example, the number of CCTAs performed annually in the United States is an estimated number because the exact number is not known).…”
Section: Discussionmentioning
confidence: 99%
“…A Canadian study showed an ICER of $57,630 per QALY for prasugrel over clopidogrel. 21) In a study in Japan, the ICER of cilostazol over aspirin for secondary prevention of cerebral infarction was 1,800,000 yen per QLAY, 22) which suggested that cilostazol was cost-effective for secondary prevention of cerebral infarction in Japan.…”
Section: Specific Cost-effectiveness Analysis In the Field Of Cardiologymentioning
confidence: 99%